2020
DOI: 10.47960/2303-8616.2020.11.25
|View full text |Cite
|
Sign up to set email alerts
|

Kako Se Sačuvati Od Stresa Za Vrijeme Pandemije Koronom

Abstract: Koronavirusna bolest je vrlo teška zarazna bolest uzrokovana teškim akutnim respiratornim koronavirusom 2 koji se neumoljivo širi od čovjeka do čovjeka u cijelom svijetu. Svjetska zdravstvena organizacija je u ožujku 2020.g. dala procjenu da se COVID-19 može okarakterizirati kao pandemija. Pandemija koronavirusom za veliku većinu ljudi predstavlja stresnu situaciju razine velikog stresnog doživljaja u kojoj može biti ugroženo zdravlje čitave populacije. Pandemija COVID-19 može izazvati snažne stresogene reakci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Our study revealed that a high level of resilience was protective against an increase in anxiety/depression when sleep quality deteriorated. Resilient individuals were adept at drawing on positive emotions in unfavorable circumstances, which may have buffered the effect of negative psychological distress and helped them to maintain better well-being outcomes [ 43 , 44 ]. Interestingly, one feature of resilience is that it can be enhanced through purposeful training [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that a high level of resilience was protective against an increase in anxiety/depression when sleep quality deteriorated. Resilient individuals were adept at drawing on positive emotions in unfavorable circumstances, which may have buffered the effect of negative psychological distress and helped them to maintain better well-being outcomes [ 43 , 44 ]. Interestingly, one feature of resilience is that it can be enhanced through purposeful training [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, women who have high-level self efficacy generally do better in self-management and own more strengthened health awareness. For pregnant women who generally encounter both psychological and physiological difficulties, high self-efficacy tend to lead to a positive adaptation following stressful situations [ 35 , 36 ]. Therefore, the present results may confirm that patients with a high self efficacy seemingly have an increased odds of recovering from low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Kupci su periodično informirani glasovnim porukama o važnosti održavanja propisane međusobne udaljenosti, kao i o važnosti dezinfekcije ruku. Održavanje propisanog razmaka te činjenica da se u prodavaonicama poticalo ljude da borave što kraće, da ne bi došlo do gužve i bliskog kontakta među njima zbog potencijalnog širenja virusa, navelo je ljude na okretanje prema kupovini na internetu (Babić, 2020).…”
Section: Pregled Odabranih Istraživanja O Utjecaju Pandemije Bolesti ...unclassified